Hyaluronic Acid–Stabilized Fe3O4 Nanoparticles for Promoting In Vivo Magnetic Resonance Imaging of Tumors - Zhang, Weijie; Zhang, Zhongyue; Lou, Shitong; Chang, Zhiwei; Wen, Baohong; Zhang, Tao (Frontiers in Pharmacology, 2022)
The use of iron oxide (Fe3O4) nanoparticles as novel contrast agents for magnetic resonance im-aging (MRI) has attracted great interest due to their high r2 relaxivity. However, both poor col-loidal stability and lack of effective targeting ability have impeded their further expansion in the clinic. Here, we report the creation of hyaluronic acid (HA)-stabilized Fe3O4 nanoparticles pre-pared by a hydrothermal co-precipitation method and followed by electrostatic adsorption of HA onto nanoparticle surface. The water-soluble HA functions not only as a stabilizer, but also a targeting ligand with high affinity for CD44 receptor overexpressed in many tumors. The re-sulting HA-stabilized Fe3O4 nanoparticles have an estimated size of sub-20 nm observed by transmission electron microscopy (TEM) imaging and exhibited long-term colloidal stability in aqueous solution. We found that the nanoparticles are hemocompatible and cytocompatible under certain concentrations. As verified by quantifying the cellular uptake, the Fe3O4@HA na-noparticles were able to target a model cell line (HeLa cells) overexpressing CD44 receptor through an active pathway. In addition, we show that the nanoparticles can be used as effective contrast agents for MRI both in vitro in HeLa cells and in vivo in a xenografted HeLa tumor model in rodents. We believe that our findings shed important light into the use of active targeting ligands to improve the contrast of lesion for tumor-specific MRI in the nano-based diagnosis systems.